Correlation of Body Mass Index with Inflammatory Markers in Rheumatoid Arthritis Patients - Tayyab, Yusra; Amir Rashid; Muhammad Javad Yousaf; Adnan Manzar; Asifa Majeed (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the correlation of body mass index with inflammatory markers among rheumatoid arthritis patients. Study Design: Comparative cross-sectional study. Place and Duration of Study: Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi Pakistan, in collaboration with the Rheumatology Department and laboratory of Pak Arab Emirates Military Hospital (PEMH), Rawalpindi Pakistan from Jan 2020 to Jan 2021. Methodology: The study sample was sixty in number and was divided into two groups. Diagnosed Rheumatoid Arthritis (RA) patients on modifying rheumatic Drugs (DMARDs) therapy constituted Group-I. At the same time, Group-II consisted of 30 healthy individuals. BMI, C reactive proteins (CRP) and erythrocyte sedimentation rate (ESR) of both groups were assessed and compared. The correlation of BMI with inflammatory markers was also assessed in both groups. Results: Sixty subjects with a mean age of 44.90±10 years were distributed evenly among two groups. Mean inflammatory markers for ESR and CRP, were 30.70±16.46 and 11.65±12.97, respectively, of Group-I. There was a significant difference in CRP and ESR (p ≤ 0.05) among the two groups. The mean BMI was 25.20±4.65, which was also raised for Group-I. BMI was positively correlated with inflammatory markers in both groups. Group-I showed a more positive correlation of BMI with ESR (r=0.23) than Group-II (r= 0.143). Conclusion: BMI is positively correlated with inflammatory status among RA patients.